Ruby Developers Guide - Feldt, Robert; Johnson, Lyle; Neumann, Michael (Elsevier Science & Technology Books, 2002)
An expert guide to Ruby, a popular new Object-Oriented Programming LanguageRuby is quickly becoming a favourite among developers who need a simple, straight forward, portable programming language.Ruby is ideal for quick and easy object-oriented programming such as processing text files or performing system management.